DINAMIKA PENGGELAPAN PAJAK: MONEY ETHICS, GENDER, RELIGIUSITAS, MATERIALISME, DISKRIMINASI, DAN SANKSI PAJAK DALAM SOROTAN WAJIB PAJAK DI KABUPATEN KUDUS - Budiman, Nita Andriyani; Alfina Darmawati; Izza Ashsifa (Merwin Publisher, 2024)
This study aims to examine and analyze the effect of money ethics, gender, religiosity, materialism, discrimination, and tax sanctions on tax evasion on individual taxpayers who are registered at the Pratama Kudus Tax Service Office. The sampling technique uses the convenience sampling method with 400 respondents. The type of research used in this research is quantitative using primary data obtained from distributing questionnaires. The method used to analyze the data is the SEM-PLS method. The results of this study indicate that money ethics, materialism, and discrimination have a positive effect, and tax sanctions have a negative effect on tax evasion, while gender and religiosity have no effect on tax evasion.